Christian counseling and psychotherapy - Benner, David G. (Grand Rapids, Mich. : Baker Book House, 1987)
"'Every therapist...is called to be an original self,' writes the editor. 'Each of us...is to strive to find and express the unique self God has called us to be. I believe that the resulting pluralism, so clearly reflected in the present volume, shows the health and vitality of current efforts of Christian psychotherapists to be distinctively and thoroughly Christian" -- BACK COVER.
Therapy with theological constructs and tactics / Harold Wahking -- Biblical themes in psychological theory and practice / J. Harold Ellens -- Toward an integral mode of psychotherapy / Arnold H. DeGraaff -- Christian counseling and human needs / Edward W. C. McAllister -- Hope in psychotherapy / Hendrika Vande Kemp -- The concept of the ideal : therapy for Christians / C. Markham Berry -- Basic biblical counseling / Lawrence J. Crabb, Jr. -- Assertiveness training / Rodger K. Bufford -- The encounter with the family of origin / Mary Vander Vennen -- Hypnosis and theology / H. Newton Malony -- Meditation and altered states of consciousness / Bill Zika -- Preventing and reversing marital burnout / David R. Leaman -- A terrible, swift sword : Christ imagery in therapy / William G. Bixler -- Treatment of multiple personality / Vance L. Shepperson --
Includes bibliographies.
Keywords: Pastoral counseling; Pastoral psychology; Psychotherapy -- Religious aspects -- Christianity